Factors influencing the clinical learning environment: a student perspective. - Vermaak, Frances Ann (My University, 2014)
Provision of a positive clinical learning environment for nursing students is and should be a critical focus area for any healthcare organisation and nursing education institution and the leadership thereof. How students are, or the lack thereof, supported and guided to become competent qualified nurse practitioners, relates to the outputs in this profession. In light of this statement it was important to determine which aspects influence nursing students‘ educational and clinical learning outcomes, and how they would impact on the quality of nursing care. The purpose of this study was to: Explore and describe the perceptions of final year nursing students registered on the Bridging Course leading to registration as a General Nurse (R682), with a Private Nursing Education Institution in Johannesburg, South Africa, who had been placed in accredited Private Hospitals (clinical facilities) with regards to the Clinical Learning Environment, Supervision and Clinical Facilitation. A cross-sectional survey was conducted using the CLES+T (Clinical Learning Environment Supervision and Teaching) questionnaire developed by Saarikoski & Leino-Kilpi (2008). Information was obtained that will provide a basis to improve the quality of educational and clinical outcomes for nursing students in the Clinical Learning Environment, through policy development in the future. Key points highlighted in the study is that the supervision in the clinical learning environment is significantly compromised and possibly as result thereof group supervision has been identified as favourable. The critical importance of clinical facilitators to students; their role and the impact they are able to have within the hospitals as a whole has also been highlighted. This is pivotal to take note of as clinical facilitators are not always considered to be of key importance to healthcare organisations in their day to day setting of hospital management and indirect payrolls. The recommendation of this study is that the focus of healthcare organisations and nursing education institutions should remain on creating a positive learning culture and environment within the hospital to improve and maintain quality nursing standards of practice for the staff and student nurses alike.
Keywords: Education, Nursing